SDSS-IV MaNGA: star formation cessation in low-redshift galaxies I: dependence on stellar mass and structural properties - Wang, Enci; Li, Cheng; Xiao, Ting; Lin, Lin; Bershady, Matthew; Law, David R.; Merrifield, Michael; Sanchez, Sebastian F.; Riffel, Rogemar A.; Riffel, Rogério; Yan, Renbin (American Astronomical Society, 2018)
We investigate radial gradients in the recent star formation history (SFH) of 1917 MaNGA galaxies with 0.01 < z < 0.14. For each galaxy, we obtain two-dimensional maps and radial profiles for three spectroscopically-measured parameters that are sensitive to the recent SFH: Dn(4000) (the 4000̊A break), EW(HδA) and EW(Hα) (equivalent width of the Hδ absorption and Hα emission line). The majority of the spaxels are consistent with models of continuously declining star formation rate, indicating that starbursts occur rarely in local galaxies with regular morphologies. We classify the galaxies into three classes: fully star-forming (SF), partly quenched (PQ) and totally quenched (TQ). The galaxies less massive than 10 10 M present at most weak radial gradients in the diagnostic parameters. In contrast, massive galaxies with stellar mass above 10 10 M present significant gradients in the three diagnostic parameters if classified as SF or PQ, but show weak gradients in D n (4000) and EW(H δ A ) and no gradients in EW(H α ) if in the TQ class. This implies the existence of a critical stellar mass (∼ 10 10 M) above which the star formation in a galaxy gets shutdown from the inside out. Galaxies tend to evolve synchronously from inner to outer regions before their mass reaches the critical value. We have further divided the sample at fixed mass by both bulge-to-total luminosity ratio and morphological type, finding that our conclusions hold regardless of these factors: it appears that the presence of a central dense object is not a driving parameter, but rather a byproduct of the star formation cessation process.